Macroprudential policy with liquidity panics - Daniel Garcia-Macia; Alonso Villacorta (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
We analyze the optimality of macroprudential policies in an environment where the role of the banking sector is to efficiently allocate liquid assets across firms. Informational frictions in the banking sector can lead to an interbank market freeze. Firms react to the breakdown of the banking system by inefficiently accumulating liquid assets by themselves. This reduces the demand for bank loans and bank profits, which further disrupts the financial sector and increases the probability of a freeze, inducing firms to hoard even more liquid assets. Liquidity panics provide a new rationale for stricter liquidity requirements, as this policy alleviates the informational frictions in the banking sector and paradoxically can end up increasing aggregate investment. On the contrary, policies encouraging bank lending can have the opposite effect.
Keywords: G01; G21; G28; 330; macroprudential policy; interbank market; liquidity panics